2020
DOI: 10.4314/bajopas.v12i1.48s
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial activities of crude <I>Moringa oleifera</I> leaves extracts on chloroquine sensitive <I>Plasmodium falciparum</I> (3D7)

Abstract: The antimalarial efficacy of crude hexane, methanol and lyophilized aqueous Moringa oleifera leaf extract was evaluated on chloroquine sensitive (CQS) strain of Plasmodium falciparum (3D7) in vitro, with a view to validate traditional use of M. oleifera as antimalarial. A dose dependent suppression of parasite growth was observed for all extracts, at microgram per mills (µg/mL) concentrations. At the lowest concentration of extract (6.25 µg/mL), the hexane, methanol and lyophilized aqueous extracts sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Regarding in vitro tests, only two studies reported the potential of M. oleifera against the parasite P. falciparum. This parasite infects humans and causes the most severe form of malaria [40,73].…”
Section: In Vivo and In Vitro Antimalarial Activity Of Moringa Oleiferamentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding in vitro tests, only two studies reported the potential of M. oleifera against the parasite P. falciparum. This parasite infects humans and causes the most severe form of malaria [40,73].…”
Section: In Vivo and In Vitro Antimalarial Activity Of Moringa Oleiferamentioning
confidence: 99%
“…In an in vitro experiment, Daskum et al [40] tested different extracts of M. oleifera leaves against the P. falciparum strain 3D7. According to these authors, although some extracts were more potent than others, all were biologically active with the following IC 50 values: hexane extract IC 50 = 3.36 µg/mL; methanolic extract IC 50 = 3.44 µg/mL; aqueous extract IC 50 = 4.09 µg/mL.…”
Section: In Vivo and In Vitro Antimalarial Activity Of Moringa Oleiferamentioning
confidence: 99%
See 1 more Smart Citation